Linear controller for wheel loader trajectory tracking - Gurko, O.; Kyrychenko, I.; Verbitsky, V.; Гурко, Олександр Геннадійович; Кириченко, Ігор Георгійович; Вербицький, Віктор Ілліч (Харківський національний автомобільно-дорожній університет, 2024)
The paper proposes a trajectory-tracking controller for an autonomous small-sized skidsteer wheel loader. The control system consists of two parts: feedforward control and feedback control. The open loop control uses the wheel loader desired velocities and accelerations. The feedback controller is a state-space feedback controller based on a linearized kinematic model.
Лінійний регулятор для забезпечення руху колісного навантажувача заданою траєкторією
Keywords: skid-steer wheel loader; trajectory tracking; feedback linearization; state-space controller; фронтальний навантажувач з боковим поворотом; відстеження траєкторії; лінеаризація зворотним зв’язком; регулятор у просторі станів.; 62-932:62.532; 10.30977/BUL.2219-5548.2024.107.0.14